Predictors of Critical Care Needs after IV Thrombolysis for Acute Ischemic Stroke - Roland Faigle; Anjail Sharrief; Elisabeth B. Marsh; R. Llinás; Victor Urrutia (2014)
Intravenous (IV) tissue plasminogen activator (tPA) is the only Food and Drug Administration (FDA)-approved treatment for acute ischemic stroke. Post tPA patients are typically monitored in an intensive care unit (ICU) for at least 24 hours. However, rigorous evidence to support this practice is lacking. This study evaluates factors that predict ICU needs after IV thrombolysis.